Feasibility of SARS-CoV-2 Antibody Testing in Remote Outpatient Trials. (6th October 2021) - Lofgren, Sarah M; Okafor, Elizabeth C; Colette, Alanna A; Pastick, Katelyn A; Skipper, Caleb P; Pullen, Matthew F; Nicol, Melanie R; Bold, Tyler D; Bangdiwala, Ananta S; Engen, Nicole W; Collins, Lindsey B; Williams, Darlisha A; et al.
Abstract: Background: During the coronavirus disease 2019 (COVID-19) pandemic, clinical trials necessitated rapid testing to be performed remotely. Dried blood spot (DBS) techniques have enabled remote HIV virologic testing globally, and more recently, antibody testing as well. We evaluated DBS testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody testing in outpatients to assess seropositivity. Methods: In 2020, we conducted 3 internet-based randomized clinical trials and offered serologic testing via self-collected DBS as a voluntary substudy. COVID-19 diagnosis was based on the Centers for Disease Control and Prevention case definition with epidemiological link to cases. A minority reported polymerase chain reaction (PCR) testing at an outside facility. We tested for anti-SARS-CoV-2 immunoglobulin via antibody detection by agglutination–PCR (ADAP) and compared the results with enzyme-linked immunosorbent assay (ELISA). Results: Of 2727 participants in the primary studies, 60% (1648/2727) consented for serology testing; 56% (931/1648) returned a usable DBS sample. Of those who were asymptomatic, 5% (33/707) had positive ADAP serology. Of participants with a positive PCR, 67% (36/54) had positive SARS-CoV-2 antibodies. None of those who were PCR-positive and asymptomatic were seropositive (0/7). Of 77 specimens tested for concordance via ELISA, 83% (64/77) were concordant. The challenges of completing a remote testing program during a pandemic included sourcing and assembling collection kits, delivery and return of the kits, and troubleshooting testing. Self-collection was successful for >95% of participants. Delays in US mail with possible sample degradation and timing of DBS collection complicated the analysis. Conclusions: We found remote antibody testing during a global pandemic feasible although challenging. We identified an association between symptomatic COVID-19 and positive antibody results at a similar prevalence as other outpatient cohorts.